2015
DOI: 10.1007/s11126-015-9361-7
|View full text |Cite
|
Sign up to set email alerts
|

Violent Video Games Don’t Increase Hostility in Teens, but They Do Stress Girls Out

Abstract: The impact of violent video games (VVGs) on youth remains unclear given inconsistent results in past literature. Most previous experimental studies have been done with college students, not youth. The current study examined the impact of VVGs in an experimental study of teens (12-18). Participants were randomized to play either a violent or non-violent video game. Teens also reported their levels of stress and hostility both before and after video game play. Hostility levels neither decreased nor increased fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 16 publications
0
15
1
1
Order By: Relevance
“…Anderson et al, ) and some arguing against such effects (Ferguson, ; Sherry, ). Further, more recent studies that are preregistered have suggested minimal video game influences on negative outcomes (Ferguson et al, ; McCarthy, Coley, Wagner, Zengel, & Basham, ; Przybylski, Weinstein, & Murayama, in press). Thus, it can be difficult to make clear statements about video game influences on aggression.…”
Section: A Brief History Of Video Game Debatesmentioning
confidence: 99%
“…Anderson et al, ) and some arguing against such effects (Ferguson, ; Sherry, ). Further, more recent studies that are preregistered have suggested minimal video game influences on negative outcomes (Ferguson et al, ; McCarthy, Coley, Wagner, Zengel, & Basham, ; Przybylski, Weinstein, & Murayama, in press). Thus, it can be difficult to make clear statements about video game influences on aggression.…”
Section: A Brief History Of Video Game Debatesmentioning
confidence: 99%
“…For example, whether increased guilt would lead players to stop killing innocent characters in the game cannot be assessed here, as this behavior was not measured. There was also a female sex bias in the sample (71% female); this could have been reflected in the results especially the sex difference in game play (American Psychological Association [APA], 2015; Ferguson et al, 2015). Plus participants’ previous video game play and experience was unclear and this has been suggested to influence results (Hartmann and Vorderer, 2010; Gollwitzer and Melzer, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, only a single preregistered study (Ivory et al 2017) has correlated video game play with negative outcomes. All other preregistered studies (e.g., Ferguson et al 2015McCarthy et al 2016) have failed to find links between VVGs and aggression. Of course, preregistration is not necessarily going to fix all problems-it is entirely possible to preregister a poorly designed study.…”
Section: Preregistered Studiesmentioning
confidence: 98%